Micro Business Empowerment: Strategies of Amil Zakat, Infaq and Sadaqah University of Muhammadiyah Yogyakarta - Sania, Ana; Sutrisno; Aslam, Ejaz (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: Poverty significantly impacts the social, economic, political, and health sectors. To reduce the poverty rate, appropriate solutions are needed, one of which is community-based microeconomic empowerment through the development of Micro, Small, and Medium Enterprises through the role of government, financial institutions, and society. Muhammadiyah amil zakat, infaq, and sadaqah institutions have Micro, Small, and Medium Enterprise empowerment programs in the economic field. Objective: This research aims to find out the micro business empowerment strategy carried out by Muhammadiyah Zakat, Infaq, and Sadaqah Institution Muhammadiyah Yogyakarta University Service Office of the micro business empowerment program carried out by Muhammadiyah Zakat, Infaq, and Sadaqah Institution Muhammadiyah Yogyakarta University in Yogyakarta. Method: This research uses a qualitative research method, a research method used to examine a natural or natural object. The researcher is the key instrument, and data collection techniques use triangulation. Result: The findings show that Muhammadiyah Zakat, Infaq, and Sadaqah Institution Muhammadiyah Yogyakarta University's micro business empowerment strategy is an integrated plan, implementation, and evaluation. Empowerment assistance, training, consultation, and motivation can help business actors develop their businesses. Implication: The research highlights the effectiveness of an integrated approach to micro-business empowerment. This suggests that combining planning, implementation, and evaluation in a cohesive strategy is crucial for successful business development. The findings provide valuable insights into how systematic support structures can significantly impact micro-businesses.